2021
DOI: 10.3847/1538-4357/ac06ca
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the New Measurement of the 12C + 12C Fusion Cross Section on the Final Compactness of Massive Stars

Abstract: We discuss how the new measurement of the 12C + 12C fusion cross section carried out with the Trojan Horse Method affects the compactness of a star, i.e., basically the binding energy of the inner mantle, at the onset of the core collapse. In particular, we find that this new cross section significantly changes the dependence of the compactness on the initial mass with respect to previous findings obtained in Chieffi & Limongi by adopting the classical cross section provided by Caughlan & Fowler. A non… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…Limongi and Chieffi [169] showed that there is a tight monotonic correlation between ξ 2.5 and m CO , which can be expressed as ξ 2.5 = 0.55 − 1.1m −1 CO , with m CO given in units of M [170]. This is in qualitative agreement with the simplified approach of Fryer et al [26], but different assumptions on carbon nuclear reaction rates might significantly affect the correlation (e.g., [171]).…”
Section: Compact Remnants and The Lower Mass Gapsupporting
confidence: 63%
“…Limongi and Chieffi [169] showed that there is a tight monotonic correlation between ξ 2.5 and m CO , which can be expressed as ξ 2.5 = 0.55 − 1.1m −1 CO , with m CO given in units of M [170]. This is in qualitative agreement with the simplified approach of Fryer et al [26], but different assumptions on carbon nuclear reaction rates might significantly affect the correlation (e.g., [171]).…”
Section: Compact Remnants and The Lower Mass Gapsupporting
confidence: 63%
“…Using solely the Hin reaction rates halves the lifetimes in comparison to the other models, due to the higher central temperature regime. Interestingly Chieffi et al (2021), using rates that are much higher than those of Caughlan & Fowler (1988) in the 0.1−1 GK range, find that C-burning occurs at lower densities (see Fig. 3 in Chieffi et al 2021).…”
Section: Stellar Modelsmentioning
confidence: 82%
“…Interestingly Chieffi et al (2021), using rates that are much higher than those of Caughlan & Fowler (1988) in the 0.1−1 GK range, find that C-burning occurs at lower densities (see Fig. 3 in Chieffi et al 2021). Indeed, since the nuclear rates are higher, a lower density is needed to reach the required amount of nuclear energy to counteract the contraction post He-b.…”
Section: Stellar Modelsmentioning
confidence: 88%
See 2 more Smart Citations